A recruiting analysis for the Kansas State College of Engineering: the financial perspective - Draheim, Jonathan (Kansas State University, 2009)
This report, “A Recruiting Analysis for the Kansas State College of Engineering: The Financial Prospective,” is an initial baseline report that measures the effectiveness of KSU COE recruiting. This analysis examines the financial factor, or how students pay for their education. Specifically, the report examines the current students in the KSU COE and how they pay for their education and then compares the information to how college students pay for their education on a national level which is outlined in a report, “How America Pays For College”, by Sallie Mae using research conducted by Gallup. Next, the report examines the reasons the current students in the KSU COE came to Manhattan to study engineering, emphasizing their geographic background as well. The results found were that more students in the KSU COE borrow funds to pay for their college education than college students on a national level. Fewer students in the KSU COE or their parents solely pay for their college education when compared to students on the national level. To gather information on how the students in the KSU COE pay for their education, 89 current students in the KSU COE were surveyed. The students were fourth and fifth year students having a high probability of finishing their degree programs than first year students. After gathering data on how this sample of 89 students paid for their education, using statistical theory, conclusions on how all the current students in the KSU COE pay for their education were made. These conclusions are compared to the payment methods for the students in the national sample.
Keywords: Financial; Perspective; Engineering, General (0537)